Rodent Models of Hemorrhagic Stroke - Strbian, D.; Durukan, A.; Tatlisumak, T. (Current Pharmaceutical Design, 2008)
Both intracerebral and subarachnoid hemorrhages are associated with high mortality and most survivors are burdened with severe disability. Currently, there is no approved treatment for intracerebral hemorrhage and surgical evacuation was not proven beneficial. Regarding subarachnoid hemorrhage, existing therapies need substantial improvement. Detailed pathophysiologic mechanisms need to be understood in order to develop novel therapeutic strategies. Hemorrhagic stroke models can help achieve both these goals and answer those questions that cannot be addressed in the clinical setting. There are several animal models of intracerebral and subarachnoid hemorrhage, each mimicking fairly reliably different aspects of the condition studied. The similarities and differences among the existing rodent models, model modifications, and some aspects concerning the choice of relevant model are discussed.
Keywords: hemorrhage